The Planar Organization of Lecithin-Cholesterol Bilayers - Donald M. Engelman; James E. Rothman (1972)
Abstract The behavior of mixed phases of dipalmitoyl lecithin and cholesterol containing less than 33 mole per cent cholesterol has been followed by wide angle x-ray diffraction. Two phases are present in this region: a pure lecithin phase and a mixed phase of lecithin and cholesterol. We propose a model in which each cholesterol is surrounded by lipid hydrocarbon chains to describe the structure of the mixed phase.